PERAN ULAMA DALAM PENINGKATAN LITERASI BUNGA BANK DI KOTA PAREPARE - Muh. Iqram (IAIN Parepare, 2025)
Public doubts about formal financial institutions are largely due to the perception that bank interest is synonymous with usury. This perception is often not accompanied by a complete understanding of the difference between interest and profit-sharing schemes in banking. Therefore, this study aims to examine the perceptions of Islamic scholars in Parepare City towards bank interest; educational strategies implemented by Islamic scholars in increasing Islamic financial literacy for the community in Parepare City; and the relevance of the level of bank interest literacy to the level of Islamic financial inclusion in the community in Parepare City. The research method used is qualitative. Primary data sources were obtained from interviews with Islamic scholars, academics, and the community of Parepare City, and secondary data were obtained from relevant literature references. Data analysis was carried out in a systematic process of data collection and summarization starting from interviews, field notes, and documents, dividing data into categories, breaking it down into units, synthesizing it, calculating it into patterns, and extracting important or complex information. The results of the study indicate that educational strategies in increasing Islamic financial literacy in Parepare City need to be directed at a contextual, applicable, and collaborative approach. Strengthening the role of Islamic scholars through training, digital da'wah, and synergy with academics and Islamic financial institutions is key to increasing public literacy regarding the Islamic financial system.